VD_FINDINFO Décision / 2014 / 534 vom 3. Oktober 2013 - VD Tribunal cantonal (2013)
TRANSACTION EXTRAJUDICIAIRE, TRANSACTION FINANCIÈRE, TRANSACTIONACCORD, RETRAITVOIE DE DROIT | 174 ch. 1 CP, 33 CP, 428 al. 2 let. b CPP (CH)